A learning agenda on gender-responsive climate-smart agriculture - Puskur, Ranjitha; Mishra, Avni (CGIAR GENDER Impact Platform, 2022)
A new learning agenda can point out learning gaps and set research priorities for organizations working to ensure that women benefit equally from climate-smart agriculture.